The Influence of Socio-Economic Factors on the Income of Traditional Fishermen in Kabila Bone District, Bone Bolango Regency - Siti Pratiwi Pakaya; Frahmawati Bumulo; Agil Bahsoan; Melizubaida Mahmud; Fatmawaty Damiti (International Journal of Economics, Management and Accounting, 2025)
The income of traditional fishermen in Kabila Bone District remains relatively low. This is caused by various fluctuating socio-economic factors, such as limited fishing equipment, the use of boat engines, and the high cost of fuel. In addition, fishermen's experience, unpredictable weather conditions, and age also affect their productivity. This study aims to determine the influence of socio-economic factors on fishermen's income. The research used a quantitative method with a sample of 74 respondents out of a population of 288 fishermen, determined using the Slovin formula. Data collection techniques included questionnaires, observation, and documentation. The results showed that socio-economic factors influence fishermen’s income by 25.2%, while the remaining 74.8% is influenced by other factors such as education and access to training on more efficient fishing techniques. In conclusion, there is a positive and significant influence between socio-economic factors and fishermen's income. This means that the better the socio-economic conditions of the fishermen, the higher their income will be.